Implementation of a Playful Microproject Based on Traditional Games for Working on Mathematical and Scientific Content - Alicia Fernández-Oliveras; María José Espigares-Gámez; María Luisa Oliveras (MDPI AG, 2021)
According to previous research, we consider it necessary to extend the use of games, as mediating elements, in the learning of STEAM (Science, Technology, Engineering, Arts and Mathematics) contents rejected by many students. For this, we have carried out an educational research project on games, with an ethnomathematical approach, since games are an important cultural sign with mathematical and scientific potentialities. We have prepared an anthropological study and an analytical one, generating a catalogue of games from different cultures. Thus, we have verified that, starting with culture, we can get to the game, but we posed the query as to whether, starting from certain games, we could achieve enculturation, by activating mathematical and scientific content in the players. To answer this query, we have created a curricular design called "playful microproject" with three traditional games from different cultures and geographical contexts. The microproject was implemented with 32 participants, from 8 to 12 years old. To analyse the results of the microproject, a case study was carried out using qualitative methodology. As part of the playful microproject, the necessary materials for each game were made by hand, and the games were then played. Both the realization of the games and the act of playing showed evidence of mathematical and scientific content, although more in the act of playing. The results revealed that: (1) the three games mobilized 21 categories of analysis, made up of scientific-mathematical content; (2) the three games proved to be equivalent in strong didactic potential; (3) that the microproject provides a valuable intercultural educational approach. The contents evidenced constitute a fundamental part of the Primary Education curriculum: classify, organize, measure, and quantify items, as well as formulate hypotheses, draw conclusions, place oneself in space, and design strategies, among others. It is concluded that these games can promote scientific-mathematical enculturation in a contextualized way.